Impact of prior CAR T-cell therapy on mosunetuzumab efficacy in patients with relapsed or refractory B-cell lymphomas - Elise A. Chong; Elicia Penuel; Ellen B. Napier; Rachel K. Lundberg; Lihua E. Budde; Mazyar Shadman; Matthew J. Matasar; Nancy L. Bartlett; Ian W. Flinn; Francesc Bosch; Keith Fay; Andre Goy; et al. (Blood Advances)
Abstract: Mosunetuzumab and other CD20/CD3 bispecific antibodies (BsAbs) have efficacy in B-cell lymphomas relapsing after or refractory to CD19-directed chimeric antigen receptor (CAR)–modified T cells (CAR-T). The optimal timing of BsAbs and biomarkers of BsAb response after CAR-T are unknown. We addressed these questions using clinical data and blood samples from patients previously treated with CAR-T and subsequently treated on a phase 1/2 study of mosunetuzumab. Thirty patients had paired samples at baseline and after 1 cycle of mosunetuzumab. The median time from CAR-T to mosunetuzumab was significantly longer for responding than for nonresponding patients (P = .006, unadjusted for multiple comparisons). Most patients (20/30) did not receive intervening therapy between CAR-T administration and mosunetuzumab. The remainder of patients received 1 intervening therapy after a protocol-mandated drug washout. After mosunetuzumab, responding patients had higher lymphocytes (995 vs 400 cells per μL; P = .02) and greater increases in CD4 and CD8 cells (median change, 73 vs –90 cells per μL [P = .005] and 243 vs –103 cells per μL [P = .004], respectively). Additionally, responding patients had an increase in activated CD8 cells (median fold change, 1.7; P = .02). Nonresponders had a relative decrease in CAR transgene levels (n = 16; P = .04). This is, to our knowledge, the first study to assess changes in lymphocytes, T cells, and CAR transgene levels in patients treated with BsAbs after CAR-T. These findings suggest an interaction between prior CAR-T and BsAb outcomes and have implications for optimal timing of BsAb after CAR-T. The trial was registered at www.ClinicalTrials.gov as #NCT02500407.